Azimuthal Equidistant Mapping and Projection of Head CT Scans for Fracture Visualization - Nicolas Hadjittoouli; Christos Nikolaou; Costas Pitris (IEEE Access)
Skull fractures of the base and facial regions of the skull are challenging to identify, even by expert radiologists. The intricate nature and subtle features of such fractures, demand meticulous attention and ample time allocation to assure effective diagnosis and positive patient outcomes. This paper introduces a novel approach, utilizing azimuthal equidistant mapping, to better visualize the skull and, thus, enhance the diagnostic speed and accuracy of skull fracture evaluation. The proposed method maps the inherently spherical shape of the skull into a planar representation, providing radiologists with an alternative view of each complete hemisphere. Applying azimuthal equidistant mapping to CT volumetric data preserves the skull’s anatomy, while fractures, which are usually perpendicular to the bone’s surface, become more visible in projection views. The enhanced visibility is particularly useful for subtle basilar or facial fractures and increases the likelihood of detection. The effectiveness of the technique was evaluated using the CQ500 dataset. Azimuthal equidistant mapping and projection can become a valuable addition to conventional radiologic evaluation, offering an alternative view for radiologists and emergency department staff, which can increase the effectiveness and time efficiency of skull fracture detection.